EVI1 overexpression reprograms hematopoiesis via upregulation of Spi1 transcription. Issue 1 (December 2018) - Ayoub, Edward; Wilson, Michael; McGrath, Kathleen; Li, Allison; Frisch, Benjamin; Palis, James; Calvi, Laura; Zhang, Yi; Perkins, Archibald
Abstract Inv(3q26) andt (3:3)(q21;q26) are specific to poor-prognosis myeloid malignancies, and result in marked overexpression of EVI1, a zinc-finger transcription factor and myeloid-specific oncoprotein. Despite extensive study, the mechanism by which EVI1 contributes to myeloid malignancy remains unclear. Here we describe a new mouse model that mimics the transcriptional effects of 3q26 rearrangement. We show that EVI1 overexpression causes global distortion of hematopoiesis, with suppression of erythropoiesis and lymphopoiesis, and marked premalignant expansion of myelopoiesis that eventually results in leukemic transformation. We show that myeloid skewing is dependent on DNA binding by EVI1, which upregulatesSpi1, encoding master myeloid regulator PU.1. We show that EVI1 binds to the −14 kb upstream regulatory element (−14kbURE) atSpi1 ; knockdown ofSpi1 dampens the myeloid skewing. Furthermore, deletion of the −14kbURE atSpi1 abrogates the effects of EVI1 on hematopoietic stem cells. These findings support a novel mechanism of leukemogenesis through EVI1 overexpression. Chr3q26 rearrangements cause overexpression of EVI1 and associate with myeloid neoplasms, but the mechanism behind this association is unclear. Here, using a novel mouse model they show that EVI1 causes premalignant myeloid expansion with suppression of other lineages through upregulation of Spi1/PU.1.